PERAN AUDITOR TEKNOLOGI INFORMASI DALAM MENGURANGI KEJAHATAN KOMPUTER - Anwar, Achmad Syaiful Hidayat (Journal of Innovation in Business and Economics, 2010)
The development of information and communication technology raise business risks, especially risks associated with security issues, privacy, accuracy and reliability of information. In this case, the factor of safety and control at the Internet-based information systems is a major and important aspect that needs to be managed effectively. This aims to protect information systems from the various possibilities of errors, fraud, crime and unethical use of information technology. The existence and implementation of Information and Electronic Transaction Act (ITE) No. 11 2008, computer forensics and the role of IT auditors is directed at efforts to reduce various forms of computer crime (computer crime), primarily in the business world.